A Mutant of Escherichia coli Defective in the Coupling of Metabolic Energy to Active Transport - Lieberman, Michael A. (1974)
The isolation of a temperature-sensitive mutant of E. coli K12 whose active transport of amino acids and sugars is not coupled to metabolic energy at 42° is described. This mutant cannot grow on succinate, fumarate, malate, or D-lactate as sole carbon source at 42° and grows on glucose at 42° with a reduced rate and yield. Efflux of accumulated substrate is also demonstrated upon heat inactivation. The defect of this mutant in both growth and transport is not due to a failure in electron transport through the respiratory chain nor the absence of Mg, Ca-ATPase activity. The mutant is thus distinct from the other energy-uncoupled mutants uncA, uncB, or etc. Analysis of spontaneous revertants indicates that the transport defect is caused by two mutations, one in the energy coupling factor gene and the other in the metC gene. The ecf(ts) mutation has been mapped to be in the 54.5- to 60-min region of the E. coli chromosome map. Possible interactions between the metC mutation and the mutated energy coupling factor protein are discussed.